1984
DOI: 10.1007/bf00553161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and sex on the plasma binding of acidic and basic drugs

Abstract: Protein binding of chlorpromazine, propranolol, meperidine, desipramine, salicylic acid and phenytoin was determined in plasma of 64 healthy volunteers (35 males and 29 females). An attempt was made to identify factors affecting the plasma protein binding of these drugs. Whereas plasma albumin levels decreased as a function of age in both sexes, alpha 1-acid glycoprotein levels increased with age, but the increase was more pronounced in males. The free plasma fraction of the acidic drugs (salicylic acid, pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 42 publications
4
27
0
Order By: Relevance
“…We were not, however, able to demonstrate any influence of age itself upon the binding of either of the propranolol enantiomers. Serum protein binding of (±)-propranolol was not statistically different in the elderly subjects, a finding which is in agreement with studies by Bendayan et al (1984) and Verbeeck et al (1984).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We were not, however, able to demonstrate any influence of age itself upon the binding of either of the propranolol enantiomers. Serum protein binding of (±)-propranolol was not statistically different in the elderly subjects, a finding which is in agreement with studies by Bendayan et al (1984) and Verbeeck et al (1984).…”
Section: Discussionsupporting
confidence: 92%
“…The main source of propranolol binding in serum has been shown to be with ot -acid glycoprotein (Vestal et al, 1979b;Rigby et al, 1985;Bendayan et al, 1984;Wallace & Verbeeck, 1987;Verbeeck et al, 1984). Studies reporting AAG concentrations in elderly subjects have been conflicting, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect of sex on HSA confirms (Davis et al, 1985;Verbeeck et al, 1984;Wallace et al, 1976 Davis et al (1985). Light smoking (3-10 cigarettes per day) did not distort the effect of age on HSA concentration or the lack of effect of age on AAG concentration.…”
Section: Discussionmentioning
confidence: 68%
“…Although others have suggested that AAG concentrations increase with increasing age in healthy subjects, the effect of age in these studies was small (Abernathy et al, 1984;Davis et al, 1985;Verbeeck et al, 1984) with little or no clinical consequences, as it has been shown that the plasma binding of lignocaine and pethidine is correlated significantly with AAG concentrations, but not with age (Davis et al, 1985;Herman et al, 1985).…”
Section: Discussionmentioning
confidence: 86%